Terminologie Numérique : Conception, Représentation et Gestion. - Vezzani, Federica. (Linguistic Insights Series, 2022)
This book focuses on digital terminology and illustrates the design and implementation of multilingual terminological databases. Through the formulation of the FAIR terminology paradigm we provide guidelines for the optimal representation of these resources in accordance with ISO standards for terminology management.